Associations of Longitudinal Fetal Growth Patterns With Cardiometabolic Factors at Birth - Huang, Jia-Shuan; Chen, Qiao-Zhu; Zheng, Si-Yu; Ramakrishnan, Rema; Zeng, Ji-Yuan; Zhuo, Can-Peng; Lai, Yu-Mian; Kuang, Ya-Shu; Lu, Jin-Hua; He, Jian-Rong; Qiu, Xiu (Frontiers in Endocrinology, 2021)
Background: Birth weight is associated with cardiometabolic factors at birth. However, it is unclear when these associations occur in fetal life. We aimed to investigate associations between fetal growth in different gestational periods and cord blood cardiometabolic factors. Methods: We included 1458 newborns from the Born in Guangzhou Cohort Study, China. Z-scores of fetal size parameters (weight, abdominal circumference [AC] and femur length [FL]) at 22 weeks and growth at 22–27, 28–36 and ≥37 weeks were calculated from multi-level linear spline models. Multiple linear regression was used to examine associations between fetal growth variables and z scores of cord blood cardiometabolic factors. Results: Fetal weight at each period was positively associated with insulin levels, with stronger association at 28–36 weeks (β, 0.31; 95% CI, 0.23 to 0.39) and ≥37 weeks (β, 0.15; 95% CI, 0.10 to 0.20) compared to earlier gestational periods. Fetal weight at 28–36 (β, -0.32; 95% CI, -0.39 to -0.24) and ≥37 weeks (β, -0.26; 95% CI, -0.31 to -0.21) were negatively associated with triglyceride levels, whereas weight at 28–36 weeks was positively associated with HDL levels (β, 0.12; 95% CI, 0.04 to 0.20). Similar results were observed for AC. Fetal FL at 22 and 22–27 weeks were associated with increased levels of insulin, glucose and HDL. Conclusions: Fetal growth at different gestational periods were associated with cardiometabolic factors at birth, suggesting that an interplay between fetal growth and cardiometabolic factors might exist early in pregnancy.